If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -30) = -6m Reorder the terms: 2(-30 + m) = -6m (-30 * 2 + m * 2) = -6m (-60 + 2m) = -6m Solving -60 + 2m = -6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6m' to each side of the equation. -60 + 2m + 6m = -6m + 6m Combine like terms: 2m + 6m = 8m -60 + 8m = -6m + 6m Combine like terms: -6m + 6m = 0 -60 + 8m = 0 Add '60' to each side of the equation. -60 + 60 + 8m = 0 + 60 Combine like terms: -60 + 60 = 0 0 + 8m = 0 + 60 8m = 0 + 60 Combine like terms: 0 + 60 = 60 8m = 60 Divide each side by '8'. m = 7.5 Simplifying m = 7.5
| 78.110-45.876= | | Y=4-3(0) | | w^2+8w+25=0 | | 16n^2-56n=-47 | | -2+0.5n=-5 | | 6+2x=6(18+6x) | | 12x+5x^2-9x^3=0 | | x^3-36x^2+72x-168=0 | | .25+14=38 | | (3x^4+3x^3-8)-(2x^2-9x+7)= | | -8k-5=2k+15 | | 19x^2+5x+0=0 | | 6w+8=4w+18 | | 14-c=5 | | (2x+y)-(x-4y)= | | x+2=7 | | (9z^3+6z)-(-2z^3-4z+8)= | | x^5+3x^4+2x^3+2x^2+6x+4=0 | | 6(2a^2+3a)=6(3-2a) | | x^5+3x^4c+2x^3+2x^2+6x+4=0 | | -17=3-4n | | 2(-5-3a)=7a+3 | | x^3+8x^2-8x-64= | | ln(x+3)-ln(x-4)=ln(x) | | -32x^2-80x-32=0 | | 3(r+4)+2(r+5)=32 | | 3x-5y=22 | | 15n^2+16n-7=0 | | (9x-2)(9x+2)= | | 27x^3+1000=0 | | -9=2-(5-z) | | 7x^2+-14x-7=0 |